The Effect of Inventory Turnover and Receivables Turnover on Profitability in Coal Sub-Sector Companies Listed on The Indonesia Stock Exchange (BEI) - Doloksaribu, Kristin Natalia; Putra, M. Syukrillah; Tampubolon, Tesalonika; Saraswati, Dwi (Accounting and Business Journal, 2024)
In the field of capital markets at panca budi university (unpab), this research aims to find out how the inventory turnover and receivables turnover methods influence the profitability of coal sub-sector companies listed on the indonesian stock exchange (bei). Participants in this research were steel industry. The research samples were ADRO, GEMS, HRUM, ITMG and PTRO companies. Individually, the inventory turnover has no effect on profitability. Individually, receivables turnover has a positive and significant influence on profitability. Together, inventory turnover and receivables turnover have a positive and significant influence on profitability.